Effects of voice on emotional arousal - Loui, Psyche; Bachorik, Justin; Li, Hui C.; Schlaug, Gottfried (Frontiers in Psychology, 2013)
Music is a powerful medium capable of eliciting a broad range of emotions. Although the relationship between language and music is well documented, relatively little is known about the effects of lyrics and the voice on the emotional processing of music and on listeners' preferences. In the present study, we investigated the effects of vocals in music on participants' perceived valence and arousal in songs. Participants (N = 50) made valence and arousal ratings for familiar songs that were presented with and without the voice. We observed robust effects of vocal content on perceived arousal. Furthermore, we found that the effect of the voice on enhancing arousal ratings is independent of familiarity of the song and differs across genders and age: females were more influenced by vocals than males; furthermore these gender effects were enhanced among older adults. Results highlight the effects of gender and aging in emotion perception and are discussed in terms of the social roles of music.